Conditional, Unconditional and Everything in Between : A Systematic Review of the Effects of Cash Transfer Programs on Schooling Outcomes - Baird, Sarah (Taylor and Francis, 2014)
Cash transfer programmes are a popular social protection tool in developing countries that aim, among other things, to improve education outcomes in developing countries. The debate over whether these programmes should include conditions has been at the forefront of recent policy discussions. This systematic review aims to complement the existing evidence on the effectiveness of these programmes in improving schooling outcomes and help inform the debate surrounding the design of cash transfer programmes. Using data from 75 reports that cover 35 different studies, the authors find that both conditional cash transfers (CCTs) and unconditional cash transfers (UCTs) improve the odds of being enrolled in and attending school compared to no cash transfer programme. The effect sizes for enrolment and attendance are always larger for CCTs compared to UCTs, but the difference is not statistically significant. When programmes are categorised as having no schooling conditions, having some conditions with minimal monitoring and enforcement and having explicit conditions that are monitored and enforced, a much clearer pattern emerges whereby programmes that are explicitly conditional, monitor compliance and penalise non-compliance have substantively larger effects (60% improvement in odds of enrolment). Unlike enrolment and attendance, the effectiveness of cash transfer programmes on improving test scores is small at best. More research is needed that examines longer-term outcomes such as test scores and, more generally, evaluating the impacts of UCTs.